Gaze and steering strategies while driving around bends with shoulders. (September 2022) - Mecheri, Sami; Mars, Franck; Lobjois, Régis
Abstract: The installation of shoulders on rural roads to create more forgiving roads encourages drivers to cut corners on right-hand bends, but the underlying mechanisms are poorly understood. Since eye movements and steering control are closely coupled, this study investigated how the presence of a shoulder influences drivers' gaze strategies. To this end, eighteen drivers negotiated right-hand bends with and without a shoulder on a simulated rural road. In the presence of a shoulder, participants modified their visual sampling of the road by directing their gaze further inside the bend. At the same time, their lane position was deviated inward throughout the bend and the vehicle spent more time out of the lane. These results suggest that the shoulder influences the visual processes involved in trajectory planning. Recommendations are made to encourage drivers to keep their eyes and vehicle in the driving lane when a shoulder is present. Highlights: With a shoulder, drivers deviated more towards the inside of right-hand bends. The presence of a shoulder increases the time spent out of the lane. Steering behaviour can be explained by the inward deviation of the driver's gaze. The presence of a shoulder alters the visual planning of the trajectory. Delineation treatments to bring the driver's gaze back to the lane are proposed.